SAR Analysis of Body Wearable Microstrip Patch Antenna Using Different Substrate Materials - Singh, Jaget (International Journal of Computer Sciences and Engineering, 2019)
Specific absorption rate (SAR) of antenna is observed when antenna is placed on body surface. For body surface a phantom model of body having dielectric characteristics of fat, skin and muscle is designed. Four textile antennas with different substrates are designed and simulated. Textile material like wash cotton, curtain cotton, polyester and polycot having different dielectric constant and thickness is used to design the patch antenna. Designed antenna simulated using CST software and analyzed on the basis of performance parameters like return loss, bandwidth and gain on flat body surface and curved surface also.